2015
DOI: 10.1111/joca.12079
|View full text |Cite
|
Sign up to set email alerts
|

Attitude toward Consumption and Subjective Well‐Being

Abstract: The current study looked at the effects of attitude toward consumption (positive or negative) on subjective well‐being. This research studied attitude toward consumption at both the personal (micro) level and societal (macro) level and subjective well‐being in terms of cognitive well‐being and affective well‐being. Results indicated that micro attitudes, whether positive or negative, were positively related to a consumer's subjective well‐being. In contrast, macro attitudes were negatively related to subjectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
1
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(102 citation statements)
references
References 60 publications
1
89
1
11
Order By: Relevance
“…However, the consequences of this trend for consumer well‐being are not well established (García‐de‐Frutos et al, ). While recent research showed that anti‐consumption tendencies in general (Lee & Ahn, ), negative attitudes toward consumption (Iyer & Muncy, ), or positive attitudes toward environmental protection (Welsch & Kühling, ) are related to increased well‐being, the presented research suggests that there can be negative well‐being consequences as well.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…However, the consequences of this trend for consumer well‐being are not well established (García‐de‐Frutos et al, ). While recent research showed that anti‐consumption tendencies in general (Lee & Ahn, ), negative attitudes toward consumption (Iyer & Muncy, ), or positive attitudes toward environmental protection (Welsch & Kühling, ) are related to increased well‐being, the presented research suggests that there can be negative well‐being consequences as well.…”
Section: Discussioncontrasting
confidence: 57%
“…While the positive consequences of green value orientations and related anti‐consumption lifestyles for the environment have been well established in the literature (e.g., García‐de‐Frutos et al, ; Haws, Winterich, & Naylor, ), potential consequences for individual consumers’ well‐being remain understudied (see Iyer & Muncy, ; Lee & Ahn, ; Welsch & Kühling, for exceptions).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, to date, academia lacks a scale that can measure anti‐consumption behaviours holistically. Hence, we mainly build on the work of Iyer and Muncy () and of Lee and Ahn () by empirically developing such a holistic scale and by focusing on simplifiers and global impact consumers.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…In general, the concept of well‐being describes the condition of individuals or groups in different areas such as their psychological, physical, social or economic status (Diener & Ryan, ; Iyer & Muncy, ; Lee & Ahn, ; Sirgy & Lee, ). Especially within the scope of marketing and psychology, the relevance of consumer well‐being has grown (Albrecht, Stokburger‐Sauer, Sprott, & Lehmann, ; Pancer & Handelman, ).…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…Does the way individuals feel and think about consumption affect their subjective well‐being? This is the basic question considered by Iyer and Muncy () in their paper entitled “Attitude toward Consumption and Subjective Well‐Being.” There are already ample studies analyzing the relationship between actual consumption, materialism, or income with well‐being (e.g., Easterlin ; Tatzel ). These studies show for example that money can buy happiness only up to a certain point and that consumer materialism tendency is associated with lower levels of subjective well‐being (Burroughs and Rindfleisch ; Kahneman and Deaton ).…”
Section: The Papersmentioning
confidence: 99%